2016
DOI: 10.1002/alr.21801
|View full text |Cite
|
Sign up to set email alerts
|

A validated case definition for chronic rhinosinusitis in administrative data: a Canadian perspective

Abstract: This study has validated several coding algorithms; based on the results a case definition of ≥2 physician claims of CRS (ICD-9 of 471.x or 473.x) within 2 years provides an optimal level of validity. Future studies will need to validate this administrative case definition from different health system perspectives and using larger retrospective chart reviews from multiple providers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…A previous study has suggested that definitions used in database studies are often too nonspecific and need to be validated. 16 Related to this is the inability of the ICD-9 coding system to distinguish CRS from recurrent acute rhinosinusitis (RARS), and it is unclear what percentage of our cohort had RARS instead of CRS. Finally, statistically significant differences with such large patient numbers may not be clinically significant.…”
Section: Discussionmentioning
confidence: 96%
“…A previous study has suggested that definitions used in database studies are often too nonspecific and need to be validated. 16 Related to this is the inability of the ICD-9 coding system to distinguish CRS from recurrent acute rhinosinusitis (RARS), and it is unclear what percentage of our cohort had RARS instead of CRS. Finally, statistically significant differences with such large patient numbers may not be clinically significant.…”
Section: Discussionmentioning
confidence: 96%
“…From there, patients with an index CRS diagnosis during that period were selected. Patients were considered as having CRS if CRS-related ICD diagnosis codes (ICD-9: 473.x, 471.x; ICD-10: J32.x, J33.x) appeared on at least two claims on two separate dates, as described by Rudmik et al [ 8 ] From this cohort, patients with continuous one-year pre-index and two-year post-index enrollment were included. A one-year pre-index washout period was implemented to capture patients with a new CRS diagnosis.…”
Section: Methodsmentioning
confidence: 99%
“…Both adult and pediatric patients with an initial CRS diagnosis, or index diagnosis, between January 1st, 2014 and December 31st, 2015 were included. Patients were considered as having CRS if CRS‐related ICD diagnosis codes (ICD‐9: 473.x, 471.x; ICD‐10: J32.x, J33.x) appeared on at least two claims on two separate dates, as described by Rudmik et al 10 The index date was defined as the first date with a claim related to a CRS diagnosis, regardless of any provider in any setting. From this cohort, patients with continuous 1‐year pre‐index and 2‐year post‐index enrollment were included, for a total of 3 years of continuous data.…”
Section: Methodsmentioning
confidence: 99%